Nuclear receptors : a practical approach - Picard, Didier (Practical approach series ;, 1999)
The steroid / nuclear receptor superfamily is a large and growing group of transcription factors that are studied by a large and varied number of basic and clinical researchers. The first two chapters describe the evolutionary biology of the superfamily and explain how to clone and characterize new receptors. Chapter 3 shows how to identify the ligands of novel receptors and chapter 4 explains the kinetic analysis of receptor interactions. In chapter 5, the reader is guided through the functional characterization of coactivators using microinjection. The next section covers receptor phosphorylation, ligand regulated transcription, and hormone resistance syndromes. Chapter 9 describes the in vitro assembly of Hsp90 complexes and chapter 10 explains yeast as a model system for looking at receptor function. The final chapter shows how heterologous proteins can be regulated by fusion to the hormone binding domain of a receptor. Nuclear Receptors: A Practical Approach is a comprehensive guide to studying members of the superfamily and will be invaluable to all researchers old and new.